The villain virus - Buckley, Michael, 1969-; Beavers, Ethen (Harry N Abrams Inc, 2013)
When a virus infects Arlington, Virginia, home of NERDS headquarters, transforming victims into criminal masterminds, it is up to Flinch to stop its spread by miniaturizing himself and entering the head of the Villain Virus's creator, Heathcliff Hodges.
Accelerated Reader
Keywords: Virus diseases -- Juvenile fiction; Superheroes -- Juvenile fiction; Spy stories; Virus diseases -- Fiction; Supervillains -- Fiction; Spies -- Fiction; Humorous stories; Spy stories; Superheroes; Virus diseases; Superheroes -- Fiction; Spy stories; Humorous fiction; Viruses -- Fiction; Spy fiction; Humorous fiction; Humorous fiction; Spy stories; Humorous fiction; Spy stories